The construction and demolition wastes in Klang Valley, Malaysia - Eusuf, Muhammad Abu; Ibrahim, Mansor; Islam, Rafikul (Malaysian Institute of Planners, 2012)
Numerous activities in construction and demolition (C&D) projects are generally considered as complex and distant that may affect surrounding environment and public health. Construction, remodelling, repairing, refurbishing or demotion works of buildings and other infrastructures such as roads generate huge amounts of hazardous and non-hazardous materials. In the present work, an attempt has been made to highlight a number of issues in C&D waste management in the Klang valley of Malaysia and which then discusses the current traditions of managing those materials in Malaysian perspectives. The paper concludes with a number of recommendations that can help to improve C&D waste management in Malaysia national perspectives.